Leadership, corruption, and inequality: Village development in a non-democratic context - Salahuddin, Salahuddin; Rifai, Rifai; Hidayat, Rahmad (The International Journal of Politics and Sociology Research, 2025)
This article explores the dynamics of non-democratic political leadership and its implications for development management in Mawu Village, Ambalawi Sub-district, Bima Regency, West Nusa Tenggara Province, Indonesia. In many developing countries, including Indonesia, authoritarian leadership is still a common practice in village governance, although its impact on village development has yet to be studied in depth. This study seeks to fill this knowledge gap by analyzing how centralized leadership impacts resource allocation, transparency, and corruption at the local level. Applying a case study approach, the authors collected the data through in-depth interviews and observations. The results show that the concentration of power in a handful of village elites results in unfair and non-transparent resource management, exacerbating socio-economic inequality in the community. Systematic corrupt practices further hamper sustainable development, erode public trust in village governance, and strengthen oppressive power structures. The findings are expected to serve as a foundation for more inclusive and accountable policy formulation in the context of village development, particularly in areas with non-democratic governance.